2015
DOI: 10.3846/13923730.2014.971129
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Effectiveness of PPP Road Infrastructure Projects by Applying Random Forests

Abstract: Abstract. Transport sector is very important for development of local economies, so it is intensively studied in different countries. Road infrastructure construction projects in many European countries are mainly carried out through various forms of Public-Private Partnership (PPP). Financial evaluation, private partner selection criteria, technical characteristics and very important focus of sustainable development components (environmental, social and economic) of PPP road infrastructure development project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Technical, financial, private partner selection and all three sustainability aspects were incorporated in the Model for effectiveness evaluation of public-private partnership (PPP) automobile road infrastructure construction projects developed by Rudžianskaitė-Kvaraciejienė et al [58]. This study revealed that the effectiveness of PPP infrastructure projects from the private partner perspective depends on technical, financial and private partner's competence factors, and project sustainability metrics as well.…”
Section: Methodology For Real Estate Investment Evaluation Based On Smentioning
confidence: 99%
“…Technical, financial, private partner selection and all three sustainability aspects were incorporated in the Model for effectiveness evaluation of public-private partnership (PPP) automobile road infrastructure construction projects developed by Rudžianskaitė-Kvaraciejienė et al [58]. This study revealed that the effectiveness of PPP infrastructure projects from the private partner perspective depends on technical, financial and private partner's competence factors, and project sustainability metrics as well.…”
Section: Methodology For Real Estate Investment Evaluation Based On Smentioning
confidence: 99%
“…The study revealed that the ensemble models provided better accuracy that the individual models. Rudžianskaitė-Kvaraciejienė et al (2015) Integrated a Random Forest algorithm with the modeling of public-private partnerships in infrastructure projects [26]. The method performed with good accuracy in the prediction process for public and private projects.…”
Section: Research Backgroundmentioning
confidence: 99%
“…The algorithm gained significant important because it is invariant under scaling and it is robust to the inclusion of irrelevant features [38]. Several studies examined the application of Random Forest in engineering applications and demonstrated its feasibility in prediction processes [26,34,35]. Under the bootstrapping method, the data during the training phase are selected randomly and independently to develop an RF model, and the data that are not involved in the selection process are named "out-of-bag" [39].…”
Section: Random Forest Modelmentioning
confidence: 99%
“…A number of studies explored RF's application in engineering applications and demonstrated its viability in prediction processes (Rudžianskaitė-Kvaraciejienė et al 2015;Yaseen et al 2019aYaseen et al , 2019bShirzad and Safari 2019). Under the bootstrapping method, data is selected randomly and independently during the training phase to develop the RF model, and data not involved in the selection process is referred to as "out-of-bag" (Catani et al 2013).…”
Section: Study Area and Modeling Datamentioning
confidence: 99%